Inhibition of Tissue Factor Pathway During Intermittent Pneumatic Compression: A Possible Mechanism for Antithrombotic Effect - Chouhan, Vibhuti D.; Comerota, Anthony J.; Sun, Ling; Harada, Russell; Gaughan, John P.; Rao, A. Koneti (Arteriosclerosis, thrombosis, and vascular biology, 1999)
Intermittent pneumatic compression (IPC) devices are an effective prophylaxis against lower extremity deep vein thrombosis. Their antithrombotic effect has been attributed to a reduction in venous stasis and enhanced fibrinolysis. The initiating mechanism for blood coagulation is the tissue factor (TF) dependent pathway, which is inhibited by tissue factor pathway inhibitor (TFPI). We have investigated the effect of IPC on the TF pathway in 6 normal subjects and 6 patients with postthrombotic venous disease undergoing IPC for 120 minutes; all subjects were studied with each of 5 IPC devices. In normal subjects and patients, plasma factor VIIa (FVIIa) activity (the activated form of factor VII [FVII]) declined from mean values ranging 51 to 65 and 50 to 53 mU/mL before IPC with different devices to 10 to 13 and 20 to 22 mU/mL at 180 minutes, respectively (P<0.001 for all groups). FVII antigen levels were unchanged. Plasma TFPI (P<0.001) rose from mean baseline values ranging 69 to 79 and 57 to 61 ng/mL to 76 to 123 and 71 to 79 ng/mL at 180 minutes in normal subjects and patients, respectively (P<0.001 for all groups). Plasma prothrombin fragment F1.2 levels showed minimal changes. There was an inverse relationship between TFPI and FVIIa in normal subjects (r=−0.31, P=0.001) and patients (r=−0.37, P<0.001). IPC results in an increase in plasma TFPI and decline in FVIIa. Inhibition of TF pathway, the initiating mechanism of blood coagulation, is a possible mechanism for the antithrombotic effect of IPC.